Effect of Different Cooling Rates on Viability and Cell Populations in Adrenal Cell Suspensions During Cryopreservation - Dudetska, G. V.; Bozhok, G. A.; Zubov, P. M.; Gurina, T. M.; Bondarenko, T. P. (Problems of Cryobiology and Cryomedicine, 2024)
Adrenal cell suspension of adult rats was assessed prior to and after cryopreservation using fluorescence microscopy, flow cytometry and histochemical staining. It was found that cooling rates render a selective effect on viability of the adrenal cells. The low cooling rates allow to preserve the highest number of nucleated cells in the post-thaw suspension.